Cloning and Characterization of 1,8-Cineole Synthase (SgCINS) Gene From the Leaves of Salvia guaranitica Plant - Ali, Mohammed; Alshehri, Dikhnah; Alkhaibari, Abeer Mousa; Elhalem, Naeema A.; Darwish, Doaa Bahaa Eldin (Frontiers in Plant Science, 2022)
Monoterpenes are one of the most common groups belonging to the terpenoid family, with a C10 structure comprising of two isoprene units. Most of monoterpenes are volatile plant compounds, and they act as signaling molecules between plants and the environment, particularly as defensive compounds against herbivores and pathogens. In this study, 1,8-cineole synthase (SgCINS) gene was identified and cloned from the leaves of Salvia guaranitica plant. To examine the role of SgCINS in insect resistance, we transformed and expressed this gene into tobacco leaves. The metabolic analysis revealed that the production of various types and amount of terpenoid was increased and decreased in SgCINS overexpression and control lines, respectively, suggesting that overexpressing SgCINS in transgenic tobacco plants lead to an increase in the production of various types of terpenoids and other phytochemical compounds. These results indicated why transgenic tobacco was highly resistant against cotton worm than the highly susceptible control plants. Our results demonstrate that the SgCINS gene can play an important role in plants against cotton worm insect attack, and pave the way for using terpenoids genes for improving resistance to insect attack in higher plants.